2003
DOI: 10.1097/01.asn.0000062962.51879.f8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Megalin in Endocytosis of Advanced Glycation End Products

Abstract: Abstract. Advanced glycation end products (AGE) are filtered by glomeruli and reabsorbed and metabolized by proximal tubule cells (PTC). In renal failure, decreased renal AGE metabolism likely accounts for the accumulation in serum that is related to uremic complications. In diabetes, AGE generation is increased, and the handling mechanisms in PTC are likely associated with the pathogenesis of tubulointerstitial injury. It is therefore important to clarify the mechanisms of the AGE metabolism to develop a stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 44 publications
0
33
0
1
Order By: Relevance
“…Increased urinary excretion in parallel with decreased circulating CML levels was also found in the long-term protocol in all age groups studied. It has been shown that AGE peptides are filtered across the glomerulus and are partially reabsorbed by the proximal convoluted tubule, while AGE-free adducts, which filter freely, are not well reabsorbed [18, 19]. Whether alagebrium itself has any direct effect on the AGE tubular transport system as well remains undetermined at present.…”
Section: Discussionmentioning
confidence: 99%
“…Increased urinary excretion in parallel with decreased circulating CML levels was also found in the long-term protocol in all age groups studied. It has been shown that AGE peptides are filtered across the glomerulus and are partially reabsorbed by the proximal convoluted tubule, while AGE-free adducts, which filter freely, are not well reabsorbed [18, 19]. Whether alagebrium itself has any direct effect on the AGE tubular transport system as well remains undetermined at present.…”
Section: Discussionmentioning
confidence: 99%
“…Megalin is a multifactorial binding receptor for a number of molecules such as protein-associated vitamins, lipids, and hormones [33,36], vitamin D carrier protein [37,38] and advanced glycation end-products, which are up-regulated in diabetes [39], but also for insulin itself [34]. Therefore, megalin may also act as a scavenger for cytokine molecules in the endocytotic process.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, both transporters of albumin (megalin and cubilin) [1] and receptors for AGEs [27] recognize multiple ligands. Thus, AGE-modified albumin binds to megalin in a model using transfected hamster ovary cells [28]. In this work, MGO-BSA appears to be taken up and processed by more than one pathway.…”
Section: Discussionmentioning
confidence: 82%